The Relationship Between Self Efficacy and Quality Of Life and Anxiety In Patients With Chronic Kidney Failure Patients Undergoing Hemodialysis Therapy At Grandmed Hospital Lubuk Pakam - Sitepu, Sari Desi Esta Ulina; Selamat Tuahta Sipayung; Raini Panjaitan; Edi Kristianta Tarigan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Chronic kidney failure is an irreversible disease, where if you have experienced this disease you cannot return to normal as before. One way that can be done to maintain the condition and function of the kidneys so that the damage does not get worse is by carrying out dialysis therapy throughout the patient's life (usually done 1 to 3 times a week) or until a new kidney donor is obtained by undergoing transplantation surgery. kidney. Situations like this interfere with the patient's quality of life and psychological disorders such as anxiety. With the emergence of feelings of anxiety and decreased quality of life, the condition of the disease experienced will worsen. One effort that can be made to manage feelings of anxiety and maintain quality of life is by exercising self-efficacy. The aim of this research activity is to see whether there is a relationship between self-efficacy and quality of life and anxiety in patients suffering from chronic kidney failure who are being treated at Grandmed Lubuk Pakam Hospital. This research is a descriptive analytical study using a cross sectional approach. There were 80 patients who were samples from the 100 patients who were the population in this study. The statistical test used in this research is the chi-square test, which shows that the p value is for quality of life (p= 0.000), and the p value is for anxiety (p= 0.003). Through these results, it can be proven that there is a significant relationship between self-efficacy and quality of life and anxiety in patients with chronic kidney failure who are undergoing hemodialysis therapy at Grandmed Lubuk Pakam Hospital.